THE IMPLEMENTATION OF ENGLISH DAY PROGRAM IN THE STUDENT'S SPEAKING SKILL AT THE ELEVENTH GRADE OF SMAN 18 MAKASSAR - Stenly Beay; Hj. Siti Haliah Batau; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2023)
ABSTRACT The aim of this study was to determine the implementation of the English day program in students' speaking skill. This research method is, applied a qualitative research, data were collected from observations, interviews, and documentation. The sample of this research is the students of class XI SMAN 18 Makassar who follow the English Club. the writer uses interview guidelines. The results of this study indicated that the English day program can improve students' speaking skills. However, the implementation of English day at SMAN 18 Makassar has not been carried out well because: some students still use Indonesian during English day, and some students are not confident to speak English with friends around them. It is recommended that the person in charge of the English Club can implement the English day program in the school environment, and tighten the applicable rules, because English day is an important program for international schools. Key words: implementation, English day, program, speaking, skill.